Afganistan a radykalizm islamski w Azji Centralnej - Grochmalski, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
For a decade all the leaders of Central Asia have agreed that the situation in Afghanistan poses a threat. It was believed to be the most significant factor of the destabilization in the region. A majority of analysts who deal with this territory agree that the Afghan war has been crucial to the revival of Islam. The states of Central Asia have recently radically changed their standpoint as a result of Islamic radicalism and the situation in Afghanistan. After September 11, 2001 the Americans have intensified their activity in this region as they have created a logistical backup for their war against the Taliban there.